Diagnostic Accuracy of Physical Examination Tests for Suspected Acute Anterior Cruciate Ligament Injury: A Systematic Review and Meta-Analysis - Shigeharu Tanaka; Yu Inoue; Yuki Masuda; Hui Tian; Hungu Jung; Ryo Tanaka (International Journal of Sports Physical Therapy)
# Background